2018
DOI: 10.1155/2018/6024874
|View full text |Cite
|
Sign up to set email alerts
|

An Enhancement Deep Feature Extraction Method for Bearing Fault Diagnosis Based on Kernel Function and Autoencoder

Abstract: Rotating machinery vibration signals are nonstationary and nonlinear under complicated operating conditions. It is meaningful to extract optimal features from raw signal and provide accurate fault diagnosis results. In order to resolve the nonlinear problem, an enhancement deep feature extraction method based on Gaussian radial basis kernel function and autoencoder (AE) is proposed. Firstly, kernel function is employed to enhance the feature learning capability, and a new AE is designed termed kernel AE (KAE).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Wang et al 2018 83 86 introduced heterogeneous transfer learning (HTL) based on stack sparse auto-encoder (SSAE). In order to solve the problem of small target domain data, they introduced a concept of distance to the center of the source and target domain to find the similarity of distribution using heterogeneous characteristics representation in HTL.…”
Section: Based Rotor-bearing System Fault Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al 2018 83 86 introduced heterogeneous transfer learning (HTL) based on stack sparse auto-encoder (SSAE). In order to solve the problem of small target domain data, they introduced a concept of distance to the center of the source and target domain to find the similarity of distribution using heterogeneous characteristics representation in HTL.…”
Section: Based Rotor-bearing System Fault Diagnosismentioning
confidence: 99%
“…Wang et al 2018 83 and Wang et al 2018, 84 employed Gaussian radial basis kernel function based autoencoder (KAEs) to enhance the feature extraction technique especially for non-linear component in bearing fault diagnosis of aircraft engine. A DNN was built with one kernel based autoencoder and multiple KAEs and result showed that the present methodology has higher accuracy because of its better feature clustering effect in feature extractions.…”
Section: Based Rotating Machines Fault Diagnosismentioning
confidence: 99%
“…In order to obtain good classification performance, the unsupervised model is often combined with the supervised model to form a semi-supervised model to achieve the purpose of adjusting the performance of the unsupervised model with the help of label information to obtain a reliable classification model. Wang FT et al [8] proposed an enhanced depth feature extraction method based on Gaussian radial basis kernel function and autoencoder. The advantage of this method is that it can obtain higher test accuracy based on fewer iterations, but the disadvantage is that it requires manual experience to adjust network parameters.…”
Section: Introductionmentioning
confidence: 99%
“…As an effective tool for dimension reduction, data mining, and machine learning, manifold learning seeks to cover the complex data processing mechanism behind the identification behavior, which can achieve the dimension reduction and feature extraction of massive fault data. erefore, it can be used as a technical means of mechanical fault diagnosis, and the fault category is better identified on the basis of maintaining the essential characteristics of fault data [6,7]. e feature extraction and fault diagnosis of mechanical equipment based on manifold learning have been a research hot spot in recent years.…”
Section: Introductionmentioning
confidence: 99%